Persepsi Orangtua tentang Bermain Berisiko pada Anak Usia Dini - Baiq Nada Buahana (Universitas Trunojoyo Madura, 2020)
Risk play is outdoors play which involves a lot of physical activity. Parents' concerns will limit the range of movement to explore when playing risky. This research explores parents 'perceptions about playing risk as viewed from the child's age, gender, and reviews parents' knowledge about playing risk. The study was conducted in Purbalingga, Indonesia. The research subjects involved 33 mothers and 33 fathers of preschool children with ages ranging from 4 to 6 years. The study findings show that mothers and fathers have the same risk playing perception. Parents provide the highest support for children's play activities at risk such as climbing and jumping from a height. As for other activities, parents have concerns about the safety of children during these activities. Judging from the age of the father and mother allow children aged 4 years with 40%, 5 years 45% and 6 years 50% while seen from jrniskelmin, parents allow boys more than girls to play at risk with percentage of 55% compared to 40%. Perceptions of parents have an impact on providing risky playing opportunities.